2006
DOI: 10.1111/j.1462-5822.2006.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Nomadic or sessile: can Kupffer cells function as portals for malaria sporozoites to the liver?

Abstract: SummaryThe initial site of replication for Plasmodium parasites in mammalian hosts are hepatocytes, cells that offer unique advantages for the extensive parasite replication occurring prior to the erythrocytic phase of the life cycle. The liver is the metabolic centre of the body and has an unusual relationship to the immune system. However, to reach hepatocytes, sporozoites must cross the sinusoidal barrier, composed of spe-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 97 publications
(146 reference statements)
0
44
2
1
Order By: Relevance
“…This study showed that anti-CD20 treatment leads to antibody-dependent phagocytosis of B cells by Kupffer cells in the liver (40). Kupffer cells usually act as silent portals of liver entry for sporozoites (41,42) but can reduce liver infection when nonspecifically activated (43). It is possible that systemic depletion of B cells by anti-CD20 treatment could activate Kupffer cells and nonspecifically reduce the parasite liver burden.…”
Section: Discussionmentioning
confidence: 85%
“…This study showed that anti-CD20 treatment leads to antibody-dependent phagocytosis of B cells by Kupffer cells in the liver (40). Kupffer cells usually act as silent portals of liver entry for sporozoites (41,42) but can reduce liver infection when nonspecifically activated (43). It is possible that systemic depletion of B cells by anti-CD20 treatment could activate Kupffer cells and nonspecifically reduce the parasite liver burden.…”
Section: Discussionmentioning
confidence: 85%
“…In the liver, they cross the vascular endothelium by passage through resident Kupffer cells in order to reach the space of Disse (1,6). This allows them free access to hepatocytes (11).…”
mentioning
confidence: 99%
“…CSP and TRAP are also crucial for sporozoite motility and infection of host cells (71). Sporozoites glide along the endothelium, then penetrate and traverse Kupffer cells to gain access to hepatocytes (72). Cell traversal seems to depend on at least two sporozoite secretory proteins, one of which contains a perforin-like membrane insertion domain that might allow the sporozoite to breach the cell membrane (73,74).…”
Section: Pathogenesis Immunity and Vaccinesmentioning
confidence: 99%